University social responsibility and brand image of private universities in Bangkok - Plungpongpan, Jirawan (2014)
This research examines the effects of University Social Responsibility (USR) on the brand image of the university. In Thailand, USR elements have been considered as mandated components quality assurance, but private universities may go beyond basic requirements to leverage advantages in a highly competitive market. This research uses qualitative interviews to explore perceptions of private university executives, M6 (high school) students, and parents of M6 students toward USR and communication about USR by private universities in Bangkok. The focus was on uncovering whether USR impacts on brand image can help move a university into the brand consideration set. The study found that university executives agreed that USR is a duty. Students are more aware of USR activities than their parents through online media and university roadshows. USR activities were not the major factor in choosing a university, but students and parents think that they help to remind of the brand, and formulate the brand consideration set. The findings could be applied to strengthen educational brand images and gained entry to the brand consideration set especially for potential customers.